Public sector accounting research in Malaysia: Identifying gaps and opportunities. - Abu Bakar, Nur Barizah; Saleh, Zakiah (Institut Perakaunan Negara, 2011)
This study aims to identify gaps that exist in academic literatures on public sector accounting (PSA) in Malaysian context. 64 relevant journal articles and dissertations dated from year 1981 to 2010 available on the web are extracted. These literatures are then being classified into four classifications including the research setting, research area and research method. Overall, the study found a scarcity of literature on Malaysian PSA. Specifically, it was found that the extant literatures do not sufficiently covers the various types of Malaysian public sector – for example statutory bodies. Studies were also not comprehensive in its coverage of different accounting issues such as accountability reporting. Further, high proportion of studies used questionnaire survey as its data collection method and a mixed method approach to research appear to be lacking. It is suggested that accounting researchers take the challenge to explore the numerous research opportunities available in this area.